Problematika liberalisasi rekrutmen sumber daya manusia perbankan Syariah di Sampang Madura - Abidin, Zainal; Haryanto, Rudy (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
The purpose of this study was to describe the problematic of liberalization of Human Resource Recruitment in sharia banking by discussing the recruitment process until the placement of employees in banking, especially in Sampang. This research used descriptive qualitative method with phenomenological approach, data collection technique is done by observation, interview and document study. The results showed that Human Resources involved in banking can be from diverse educational background, not only from sharia banking education or a cognate education, such as economics and business, except health and literature graduated who cannot follow the admission selection. There is no protection against prospective employees from economic and business graduation and sharia banking. The recruitment process is done by the above office with a process that has already passed the standard. Structuring of Human Resources in sharia banking Sampang is based on organizational structure that has been standard with job description that has been arranged so that managers can easily place an employee in Islamic banking at Sampang Madura